An empirical study on the impact of digital economy development on the upgrading and optimization of industrial structure - Zhang Chao (E3S Web of Conferences, 2021)
As an important driving force and new kinetic energy, digital economy is promoting the development of economy in the direction of high quality, and brings new opportunities and challenges to the development of real economy and the upgrading and optimization of industrial structure. Therefore, this paper measures the digital economy from the two aspects of “digital industrialization” and “industrial digitization”, and selects the data of 30 provinces and cities from 2012 to 2019 to empirically study its impact on the upgrading and optimization of China’s industrial structure. Through the research, it is found that digital economy can indeed improve the level of upgrading and optimization of industrial structure. At the same time, further analysis shows that the degree and mechanism of improving the level of eastern, central and western regions will be different according to different regions. Finally, according to the research results, this paper puts forward some countermeasures and suggestions to promote the development of digital economy and the optimization and upgrading of industrial structure in China.